Faktor Risiko Kanker Payudara pada Wanita Muda di RSUD Al Ihsan Tahun 2025 - Eriantiningrum, Salsabila; Sumantri , Agung Firmansyah; Maharani, Winni (Jurnal Riset Kedokteran, 2025)
Abstract, Currently, the world is experiencing a shift in disease trends, from predominantly infectious diseases to an increasing prevalence of non-communicable diseases (NCDs). One of the leading causes of death among NCDs is breast cancer, which ranks as the second leading cause of mortality worldwide. The incidence of this disease is rising among young women, triggered by various risk factors that contribute to the development of cancer cells, such as Body Mass Index (BMI), family history, early menarche, long-term use of hormonal therapy, smoking habits, and marital status. This study aims to describe the risk factors associated with breast cancer in young women at RSUD Al Ihsan, West Java, during the year 2025. This study is a descriptive study with a cross-sectional approach was conducted using secondary data obtained from the medical records of young female breast cancer patients at RSUD Al Ihsan, with a total of 64 respondents. The results indicate that the majority of respondents had a normal BMI with an average of 19.30, were married (96.88%), non-smokers (93.75%), did not undergo hormonal therapy (71.88%), had no family history of breast cancer (73.44%), and did not experience early menarche (98.44%). These findings suggest that most respondents did not present classical risk factors such as a family history of breast cancer, early menarche, smoking habits, or long-term hormonal therapy. This indicates the potential involvement of other factors, such as diet, physical activity, environmental exposure, or more complex genetic predispositions. Abstrak, Saat ini, dunia mengalami perubahan tren penyakit, dari dominasi penyakit menular menjadi peningkatan penyakit tidak menular (PTM). Salah satu PTM yang menjadi penyebab utama kematian adalah kanker payudara. Penyakit ini merupakan penyebab kematian kedua di dunia dan semakin banyak ditemukan pada wanita usia muda. Beberapa faktor risiko dapat memicu perkembangan kanker payudara, di antaranya Indeks Massa Tubuh (IMT), riwayat keluarga, menarche dini, penggunaan obat hormonal jangka panjang, kebiasaan merokok, dan status pernikahan. Studi ini bertujuan untuk menggambarkan faktor risiko kejadian kanker payudara pada wanita muda di RSUD Al Ihsan, Jawa Barat, periode tahun 2025. Penelitian ini menggunakan metode deskriptif dengan pendekatan cross-sectional. Data dikumpulkan dari rekam medis pasien kanker payudara wanita usia muda di RSUD Al Ihsan. Total subjek penelitian sebanyak 64 responden. Mayoritas responden memiliki IMT normal dengan rata-rata 19.30, sudah menikah (96.88%), tidak merokok (93.75%), tidak menjalani terapi hormon (71.88%), tidak memiliki riwayat keluarga dengan kanker payudara (73.44%), dan tidak mengalami menarche dini (98.44%). Hasil penelitian menunjukkan sebagian besar responden tidak memiliki faktor risiko klasik. Ini menunjukkan kemungkinan peran faktor lain seperti pola makan, aktivitas fisik, paparan lingkungan, atau predisposisi genetik dalam kejadian kanker payudara.